Strengthening of accountability systems to create healthy food environments and reduce global obesity. Issue 9986 (20th June 2015) - Swinburn, Boyd; Kraak, Vivica; Rutter, Harry; Vandevijvere, Stefanie; Lobstein, Tim; Sacks, Gary; Gomes, Fabio; Marsh, Tim; Magnusson, Roger
Summary: To achieve WHO's target to halt the rise in obesity and diabetes, dramatic actions are needed to improve the healthiness of food environments. Substantial debate surrounds who is responsible for delivering effective actions and what, specifically, these actions should entail. Arguments are often reduced to a debate between individual and collective responsibilities, and between hard regulatory or fiscal interventions and soft voluntary, education-based approaches. Genuine progress lies beyond the impasse of these entrenched dichotomies. We argue for a strengthening of accountability systems across all actors to substantially improve performance on obesity reduction. In view of the industry opposition and government reluctance to regulate for healthier food environments, quasiregulatory approaches might achieve progress. A four step accountability framework (take the account, share the account, hold to account, and respond to the account) is proposed. The framework identifies multiple levers for change, including quasiregulatory and other approaches that involve government-specified and government-monitored progress of private sector performance, government procurement mechanisms, improved transparency, monitoring of actions, and management of conflicts of interest. Strengthened accountability systems would support government leadership and stewardship, constrain the influence of private sector actors with major conflicts of interest on public policy development, and reinforce the engagement of civil society in creating demand for healthy food environments and in monitoring progress towards obesity action objectives.